Analisis pengaruh current ratio, debt equity ratio, earning per share, kurs dan tingkat inflasi terhadap harga saham pada perusahaan manufaktur di lq45 - Ibrahim Nurdin ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2015)
This research is an explanatory research conducted on the manufacturing sector in LQ45 during 2010-2014. The research entitled "Analysis of the Influence of Current Ratio, Debt Equit Ratio, Earning per Share, exchange rate and inflation rate towards Stock price in Manufacture Companies Listed in LQ45”. The purpose of this research is to analyze the influence Current ratio, debt equity ratio, earning per share, exchange rate and inflation rate on stock price manufacture companies in LQ45. This research uses multiple regression analysis as model to test the hypothesis. The population in this research are all manufacture companies listed in LQ45 from 2010 until 2014 with the total 12 companies. The samples were taken by using purposive sampling. However, the final samples in this research are 7 companies. The result of this research show that debt equity ratio and earning per share had positive effect on stock price, while current ratio, exchange rate and inflation rate had no significant effect on stock price.Keywords : stock prices, current ratio, debt equity ratio, earning per share,                exchange rate, inflation rate